The Different Models of Community Eldercare Service in China - Zhang, Lei; Yang, Jinwei (Frontiers in Sociology, 2019)
The study examines the development trajectory of community eldercare service and how the local governments pursue the policy innovation in delivering community eldercare in China. After reviewing the pilot practice in different localities, this paper will attempt to compare and classify the models of community eldercare service and find out the different features and outcomes of the models. Through the comparative study of community eldercare model this paper will provide the policy implications for national community eldercare system building and policy suggestions for further development..